Complejo interactivo de energías alternativas: Plan parcial tejidos vitales (2017)
The project responds to the challenge of supplying in an integral way the need to establish an infrastructure model for transport, projecting demand for the next 20 years and responding to urban social and environmental conditions of the place. The interactive alternative energy complex is a commitment to the promotion and development of a sustainable economy and the initiation of the replacement of oil-based energy sources with clean and renewable sources in one of the most extreme climates in the world country.